Wider area validation and economic analysis of adaptable IPM technology in bell pepper (Capsicum annum) - SARDANA, H R; BHAT, M N; SEHGAL, MUKESH (The Indian Journal of Agricultural Sciences, 2012)
Field experiments were conducted in bell pepper (Capsicum annum var. frutescens L.) during 2007–10 at Daha-Jagir, Karnal, Haryana with a view to study the validation and economic viability of adaptable IPM technology in a farmers’ participatory approach. The IPM technology for bell pepper crop comprising raising healthy nursery using soil solarization and mixing of Trichoderma harzianum (c.f.u. 2 × 109) along with FYM (@ 10 g/ 100 g FYM/m2); seedling dip in Pseudomonas fluorescence, installation of delta traps @ 2/acre, one or two sprays of neem (Neem Baan @ 10 ml/litre) against aphids in early stages, erection of pheromone traps @ 5/ha, application of spinosad 45 SC @ (75 g ai/ha or 0.5 ml/litre) for thrips, collection and destruction of borers and disease affected fruits, five releases of egg parasitoid Trichogramma chilonis based on pheromone monitoring, two sprays of HaNPV 250 LE/ha in evenings with UV protectant, one spray of ecofriendly emmamectin benzoate 5 WDG @ 0.25 g/lit of water, two to three need based sprays of chemical pesticides like indoxacarb 14.5 SP @ 500 g ai/ha or rynaxpyr 18.5 SC @ 3.5 ml /litre of water and carbendazim + mancozeb 75 SP @ 0.2% etc. was very effective in reducing the incidence of pests and minimizing the yield losses. The adoption of IPM technology resulted in reducing the number of chemical  sprays to 4–5 from 12–14 in non-IPM fields with higher fruit yields of 14.07–24.35 and 21.63 tonnes/ha in IPM and 12.20, 15.58 and 18.0 tonnes/ha in non-IPM fields and with higher CBR of 1:1.99, 1:3.29 and 1:2.81 in IPM than 1:1.48, 1:1.70 and 1:2.30 in non-IPM.